An Analysis of Critical Thinking Skills and Nutrition and Health Literacy of Students - Siti Fathonah; Edy Cahyono; Sarwi Sarwi; Noer Hayati Lestari; Retno Sri Iswari; Sri Haryani (Universitas Negeri Semarang, 2021)
This study used a cross sectional design, which focused on the relationship between critical thinking skills and nutrition and health literacy. The research subjects were 102, first year (37 students) and second year (65 students) Culinary Education students. Critical thinking skills level was obtained by providing multiple choice tests, with score grade of 1-4. Nutrition and health literacy level was obtained by providing questionnaires from Nlit and The Newest Vital Sign. The relationship degree was analyzed by using Pearson correlation. Meanwhile, the difference in year of admission and gender were tested using independent sample t-test. The results showed that there was a correlation of r = 0.304 with p = 0.002 for the critical thinking skills and nutrition and health literacy. The critical thinking skills of first year students (65.7 ± 4.5, very high) was not significantly different (p = 0.735) with second year students (66.0 ± 4.1, very high). Nutrition literacy and health of first year students (45.9 ± 9.8, high) were significantly different (p = 0.045) with second year students (49.2 ± 6.5, high). The critical thinking skills of male students was higher (68.5 ±3.4, very high) and not significantly different from that of female students (65.5 ± 4.3, very high). The nutrition and health literacy of male students (68.5 ± 3.4, very high) was higher and significantly different than female students (65.5 ± 4.3, very high).